Pattern Recognition of Melaleuca cajuputi Powell Essential Oils Fingerprint in Terengganu, Malaysia Using Chemometric Approach - Hanif Abdullah, Mohd; Juahir, Hafizan; Lananan, Fathurahman; Khairul Amri Kamarudin, Mohd; Ghazali, Adiana; Azemin, Azierah; Jima Abd Wahab, Noor; Musliha Mat-Rasid, Siti; Hafiz Md Saad, Muhammad (International Journal of Engineering and Technology, 2018)
Cajuputi essential oil is extracted from the leaves of Melaleuca cajuputi Powell. This study is performed to spatially classify the variation of Melaleuca cajuputi essential oil fingerprint based on different sampling location using chemometric technique along Terengganu coastal area. Discriminant Analysis (DA) successfully discriminate 10 fingerprint of essential oil into three different groups with three significant peaks in FTIR analysis. Hierarchical agglomerative cluster analysis (HACA) successfully grouped the 10 sampling stations into three groups (cluster A, B and C).Classification criteria is based on the intensity movement of functional group either bending or stretching of the essential oil compound Multiple linear regression (MLR) was used to develop an equation model that explains the prediction of species fingerprint in each cluster by different locations. Â